Desain dan Uji Kinerja Alat pengering Hybrid Dengan Efek Cerobong Tipe Tumpukan untuk Pengeringan Biji Kopi Arabika - Irwansyah Irwansyah; Leopold Oscar Nelwan; Dyah Wulandani (Jurnal Keteknikan Pertanian, 2019)
Artificial drying method for arabica coffee beans requires a large consumption of electrical energy. Electricity is needed to rotate the blower which functions to circulate hot air to the dryer so that it can evaporate some of the water contained in the coffee beans. Most of the arabica coffee producing areas in Aceh province have not been reached by the electricity network so the use of artificial dryers cannot be used. To overcome this obstacle, the air flow circulation system with chimney effect can be used to drain dry air. The aim of this research is to design a chimney effect hybrid dryer which is heat source from solar and biomass energy, to test the performance of the dryer and compare it with the sun drying method. Parameters observed were temperature, moisture content and specific energy consumption of solar radiation and biomass. Dryer capacity is 5 kg of arabica coffee beans. The results showed that the chimney effect hybrid dryer can be used to dry 5 kg of coffee beans. The drying show that drying temperature on the dryer chamber ranged between 37.3-60.9°C. To reduce the moisture content of coffee beans from 52.5 to 12.8% bb, it was take 16-17 hours, while the sun drying method takes up to 46 hours (6 days). The total specific energy consumption of hybrid dryer was 57.1 MJ/kg of water vapor, while the specific energy consumption of the drying method was 59.4 MJ/kg of water vapor.